The Role of Community-Based Nonformal Education in Maintaining the Sawai Language in Central Halmahera: An Ecolinguistic Perspective - Jamal, Agus Hi; Yanti, Prima Gust; Tarmini, Wini (Journal of Nonformal Education, 2026)
Background - Local-language maintenance depends not only on the number of speakers but also on whether a language continues to have meaningful social domains, intergenerational transmission, and community ownership. In Central Halmahera, the Sawai language remains an important marker of identity, yet its everyday use among younger community members is narrowing as Indonesian becomes more dominant in schooling, digital media, and daily interaction. Research Urgency - Previous language-maintenance initiatives in Indonesia have largely emphasized school-based local-content curricula and government revitalization programs. Less attention has been given to community-based nonformal education as a flexible learning ecology that can connect elders, families, tutors, cultural leaders, and young learners outside compulsory schooling. Research Method - This study used a qualitative case-study design in Kobe Village, Weda Tengah District, Central Halmahera Regency, North Maluku. Participants were selected purposively from community learning organizers, tutors or facilitators, customary and community leaders, and learners. Data were generated through in-depth interviews, participatory observation, and analysis of learning and community documents. The data were organized, coded, categorized, and interpreted thematically. Source and method triangulation were used to compare accounts across participant groups and data types. Research Findings - The findings indicate that Sawai continues to be used in customary events, family communication, oral traditions, and some intergenerational interactions, but its use among children and adolescents is becoming less regular. Existing transmission activities are mostly incidental and depend on families or cultural figures rather than a sustained community learning program. Community members prioritized oral competence, everyday communication, customary expressions, folklore, and knowledge of local flora and fauna as learning content. These findings show that community-based nonformal education can support language maintenance by creating recurring domains of use, organizing intergenerational learning, and linking language with culture and the local environment. The study formulates a seven-component framework covering needs and vitality mapping, learning outcomes, place-based content, participatory strategies, learning media, authentic assessment, and community partnership. Research Conclusion - Community-based nonformal education can function as an ecological space for Sawai-language maintenance when activities are regular, community-owned, intergenerational, and connected to everyday cultural and environmental practices. The proposed framework requires piloting before claims about its effectiveness can be made. Research Novelty/Contribution - This study connects nonformal education and ecolinguistics by positioning language maintenance as the construction of a community learning ecosystem rather than merely the addition of a local-language subject. It offers a context-sensitive framework for PKBM, cultural studios, village learning houses, and customary communities working with minoritized local languages.